Peningkatan Keterampilan Pembuatan Frozen Food Bagi Anggota Dharma Wanita Persatuan Pemerintahan Kabupaten Jember - Rindiani Rindiani; Galih Purnasari (Journal of Community Development, 2022)
Shrimp and pumpkin are local foods in Jember Regency which can be processed into food products such as dumplings and donuts. These products can be processed into frozen food. Frozen food has the opportunity to be a business to improve family welfare. Women also play a role in improving the welfare of their families. Training and demonstrations in making frozen food dumplings from shrimp and donuts from pumpkin were conducted to women who are members of Dharma Wanita Persatuan Jember Regency. All participants were able to make shrimp dumplings and pumpkin donuts well. The next training plan is packaging techniques training using a vacuum sealer, so that participants can pack their homemade products in good packaging, do not leak and have high durability when marketed. Participants also need training on how to market products so that the rproducts can be well absorbed by the market.